Bridging the Gap: Empowering Traditional Artisans and Artists Through Digital Marketplaces in Developing Economies (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Traditional artisans and artists in developing economies continue to face limited access to wider markets despite growing interest in authentic and culturally rooted products. In Baguio City, Philippines, a UNESCO Creative City for Crafts and Folk Art, many artisans still depend on local exhibitions, tourism, community events, and informal selling networks. Digital marketplaces may help expand visibility and income opportunities, but participation remains shaped by issues of trust, accessibility, logistics, digital confidence, and cultural representation.This study examines the perspectives, readiness, and support needs of artisans and artists in Baguio City regarding digital marketplace participation. A qualitative descriptive research design was used, supported by descriptive survey indicators and thematic analysis. Data were gathered from eighteen artisans and artists representing visual arts, jewelry, weaving, and other creative sectors. The findings show that participants generally have strong digital readiness and interest in online selling, especially when supported by training, secure payment systems, transparent logistics, and culturally responsive platform features.Thematic analysis identified five major themes: digital readiness and willingness to adapt, trust and security concerns, market visibility and audience reach, cultural preservation through storytelling, and the need for institutional and community support. The study contributes to current discussions on digital inclusion and creative economies by showing that meaningful digital participation requires more than access to technology. It also requires trust-building, cultural sensitivity, practical support, and community-centered platform design.The paper recommends the development of culturally responsive digital marketplace systems supported by local government, academic institutions, creative organizations, technology partners, and artisan communities. These systems should prioritize accessibility, transparency, digital literacy, authenticity protection, and ethical representation of traditional and indigenous crafts.